Keefektifan Model Project Based Learning dan Pemanfaatan Ecobrick dalam Meningkatkan Literasi Sains pada Anak Usia Sekolah Dasar di Komunitas Harapan Kota Semarang - Mustaghfiroh, Khoerul; Purnamasari, Iin; Azizah, Mira (CV. Supernova Office Stationary and Printing, 2023)
The background that prompted this research was the low level of child scientific literacy in Harapan Community, Semarang City. This is caused by an unsupportive environment and learning that is not contextual in optimizing children's abilities. The problem in this research is whether the project-based learning model and the use of ecobricks can increase scientific literacy in elementary school-age children in Harapan Community, Semarang City. The goal to be achieved in this research is to determine the effectiveness of implementing a project-based learning model and the use of ecobrick in increasing scientific literacy in elementary school-age children in Harapan Community, Semarang City. This type of research is experimental research in the form of a Pre-Experimental Design with a One-Group Pretest-Posttest Design. The research population was all high school-age children in Harapan Community who had known that their level of scientific literacy was still low. The sample in this study were all children in the Harapan Community who were of high class age with a total of 12 children. The results of the study show that there is effectiveness in using the Project Based Learning learning model and using ecobrick to increase scientific literacy in elementary school-aged children in Harapan Community, Semarang City. It can be proven by calculating the paired sample t-test, obtained a calculated value of 7.881 with db = n1–1 = 12-1 = 11 and a significant level of 5% = 0.05, obtained a ttable of 2.201. So tcount ? ttable = 7.881 ? 2.201 so H0 is rejected and H1 is accepted, meaning that there is effectiveness from the application of the Project Based Learning learning model and the use of ecobrick in increasing the scientific literacy of elementary school-age children in Harapan Community, Semarang City.